Justification of kinematic parameters of coupling for wide-span row-crop unit - Bulgakov, Volodymyr; Nozdrovicky, L.; Movchan, Vitalii; Мовчан, Віталій Федорович; Мовчан, Виталий Федорович; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2019)
Effective use of the KhTZ-160 tractor is possible, with the specified width, combining the implementation of the main technological process with an additional, i.e. sowing with cultivation. Shows the results of calculations of the transverse displacements of the working bodies as a function of their placement along the width of unit and along its length relative to the transverse geometric axis that passes through the kinematic the center of the tractor without taking into account the curvature of the trajectory of tractor and possible changes in the position of kinematic center along the unit. The largest values of the transverse displacements of the working bodies, which are placed at a distance of 2.6 m, i.e. at the machine which is attached to the rear hinged system of the tractor, reach 14.5 cm at maximum angles of rotation of the unit (3 degrees). The smallest transverse movements of the working bodies are observed when placed on a geometric axis that passes through the axis of the rear wheels (less than 1 cm). The lateral movements of working bodies of 18-row wide-coverage row-crop unit depending on the tractor turning angle and their placement in the unit are considered. Kinematic parameters and coupling scheme are recommended.
Keywords: unit; tractor; coupling; working bodies; placement; angle; deviation; scheme